A MATERNIDADE NO SISTEMA PENAL BRASILEIRO: uma análise dos referenciais jurídico-políticos e dos desafios do Projeto Mulheres Livres - BONGO, Dominick Luzolo Veloso (2022)
This Dissertation has as its main theme the maternity in the Brazilian penal system, having as an empirical parameter the Free Women Project (Projeto Mulheres Livres), which was created in 2017 by the National Penitentiary Department-DEPEN (Departamento Penitenciário Nacional), and aimed to promote policies that cover women deprived of liberty who are pregnant, or who are mothers of children in early childhood age, to mitigate the social impacts resulting from incarceration, prioritizing the well-being of the child. Its general objective is to analyze the legal and political foundations in the formulation of the “Free Women” Project as a public policy aimed at reducing the vulnerability of families who have mothers deprived of their liberty, considering: the socio-historical context of the process of formulating the “Free Women Project.”; the legal and political references that supported the formulation of the policy, and finally, to evaluate the elements that constitute the policy, and the challenges to implement them. With a qualitative approach, it was used a bibliographic and documentary research, as well as secondary data analysis. Based on Bourdieu's reflexive sociology, in which it is understood that it is necessary to distinguish rigidity from scientific rigor, seeking to use the various methodological resources available in the various related contexts, and also in the analysis of discourse supported by Foucaultian literature, it is considered that the public policies aimed at maternity in the penal system are formulated in the context of different political and legal grounds and interests. As a result, it is observed that the absence of systematization of data from the beneficiary public makes it difficult to assess the real conditions of maternity in the criminal system, thus preventing the referral to social protection services and the labor market, goals set by the Project for social reintegration based on the best interests of the child and the effectiveness of the policy.